Correlation of Knowledge With The Attitude of Head Family About Clean And Healthy Behaviour (Phbs) In Cilembang Cihideung Tasikmalaya - Erinda Nur Pratiwi; Iis Sopiah Suryani; Lina Marlina; Risma Fitria (Journal of Midwifery, 2018)
Families can implement healthy ways of life by maintaining, and improving their health by providing learning experiences, opening communication, providing information and education so that Clean and Healthy behaviour (PHBS) can be achieved. This study aims to determine the relationship of knowledge with the attitude of the head of the family about Clean and Healthy Life Behavior in Cilembang, Cihideung District, Tasikmalaya City. The method used in this study is an analytical survey using a cross sectional approach. The population in this study were all family heads totaling 232 families. The sampling technique in this study uses cluster random sampling technique, which is as many as 70 family heads. The type of data used in this study is primary data. The instrument used was a questionnaire which was made by the author and tested for validity and reliability. Data analysis techniques using univariate (Frequency Distribution) and bivariate (chi-square) techniques. From the results of the study that most respondents have a good level of knowledge about Clean and Healthy Life Behavior, which is 69 people (98.6%). And the attitude of respondents towards Clean and Healthy Life Behaviors mostly have good attitude, that is 69 people (98.6%), with the results of x2 shows Pvalue = 0.903> 0.05. The conclusion of this study is that there is no significant relationship between knowledge with the attitude of the head of the family about Clean and Healthy Life Behavior. The results of this study are expected to improve the knowledge and attitudes of family heads regarding Clean and Healthy Life Behavior.